Effect of Parenting Parents on Early Childhood Development - Dafid Efendi; Abdul Rahim (Universitas Negeri Padang, 2019)
Parenting is an important component that must be owned and obtained by Early Childhood, early childhood as we know it is very easily influenced by environmental factors, early childhood is very easy to digest and capture everything that is seen and heard, one of experts have said that early childhood is like a dry sponge dropped into a liquid where the sponge will absorb all the liquid that is approached and confronted with this sponge, as a means or interpretation of this sponge compared to early childhood where early childhood is easy once he catches everything he discovers and he doesn't care whether what he catches is good or bad as well as what he sees he will catch and imitate it.Keywords: Parenting, Early Childhood